Renewables 2016 : global status report - key findings (REN21 Secretariat ParisFR, 2016)
Reflects diverse view points from both private and public sector actors, serving to dispel myths about renewable energy and to catalyse polic change.
Keywords: RENEWABLE ENERGY SOURCES